Active defense eaudiobook - Eason, Lynette (Danger Never Sleeps, 2021)
As a former field surgeon in Afghanistan, Heather Fontaine is used to life-or-death situations. She just didn't expect them to follow her home. When she returns from a party to find that someone has broken into her house—and threatened her friends—she assumes it is the stalker who has been following her and creeping her out. She hopes to find safety and peace of mind by leaving the city and hiding out in a small town. But trouble has followed her even there. Luckily, a stalker isn't the only one watching Heather. Travis Walker has been secretly watching out for her for weeks. As owner of his own security agency, it's what he does. Together, Travis and Heather must figure out who wants her dead—and why—before it's too late.